Brucella Outer Membrane Lipoproteins 19 and 16 Differentially Induce Interleukin-18 Response or Pyroptosis in Human Monocytic Cells. (20th May 2021) - Ren, Hui; Yang, Heng; Yang, Xin; Zhang, Guoxia; Rong, Xia; Huang, Jiaheng; Zhang, Ling; Fu, Yongshui; Allain, Jean-Pierre; Li, Chengyao; Wang, Wenjing
Abstract: Background: Brucella species are Gram-negative intracellular bacteria that causes severe inflammatory diseases in animals and humans. Two major lipoproteins (L19 and L16) of Brucella outer membrane proteins were studied to explore the association with inflammatory response of human monocytes (THP-1). Methods: Activated THP-1 cells induced with recombinant L19 and L16 were analyzed in comparison with unlipidated forms (U19 and U16) and lipopolysaccharide (LPS) of Brucella melitensis, respectively. Results: Secretion of inflammatory factors tumor necrosis factor-α, interleukin (IL)-6, and IL-1β was significantly increased from L19, L16, or both stimulated THP-1 cells. High secretion of IL-18 was detected only from L19-induced cells. Signaling of those cytokine responses was identified mainly through the P38-mitogen-activated protein kinase pathway, and signaling of L19-induced IL-1β response partly occurred via necrosis factor-κB. While exploring different forms of IL-18, we found that L19-induced production of active IL-18 (18 kD) occurred through upregulating NLRP3 and activating caspase-1, whereas L16-induced production of inactive IL-18 fragments (15 kD and 16 kD) occurred through activating caspase-8/3. We also found that L19 upregulated phosphorylation of XIAP for inhibiting caspase-3 activity to cleave IL-18, whereas L16 activated caspase-3 for producing GSDME-N and leading to pyroptosis of THP-1 cells. Conclusions: Brucella L19 and L16 differentially induce IL-18 response or pyroptosis in THP-1 cells, respectively. Abstract : This study explored the mechanism of Brucella lipoproteins L19- and L16-induced inflammatory response in macrophages. L19 stimulated active IL-18 through caspase-1 and XIAP phosphorylation, whereas L16 induced inactive IL-18 and pyroptosis via caspase-3 and GSDME-N.